2019
DOI: 10.1039/c9na00104b
|View full text |Cite
|
Sign up to set email alerts
|

Assessing size-dependent cytotoxicity of boron nitride nanotubes using a novel cardiomyocyte AFM assay

Abstract: A novel AFM-based assay was in agreement with traditional cytotoxicity assays and exposed a size-dependent toxicity of boron nitride nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 40 publications
(89 reference statements)
0
28
0
Order By: Relevance
“…[138] A recent study used AFM based cytotoxicity technique and showed that long BNNTs (>500 nm) are more cytotoxic than shortened BNNTs. [139] The latest BNNT report (June 2020) from the National Institute for Occupational Safety and Health (NIOSH) is a BNNT study in vitro and noted that higher doses of BNNT in pulmonary exposure can cause damage. [140] This biocompatibility is still being extensively studied and has not been conclusive due to the varying models.…”
Section: Toxicitymentioning
confidence: 99%
“…[138] A recent study used AFM based cytotoxicity technique and showed that long BNNTs (>500 nm) are more cytotoxic than shortened BNNTs. [139] The latest BNNT report (June 2020) from the National Institute for Occupational Safety and Health (NIOSH) is a BNNT study in vitro and noted that higher doses of BNNT in pulmonary exposure can cause damage. [140] This biocompatibility is still being extensively studied and has not been conclusive due to the varying models.…”
Section: Toxicitymentioning
confidence: 99%
“…While this piezoceramic has been found to promote the proliferation, attachment, and osteogenic differentiation of MSCs, several studies have also reported their negative influence over chondrocytes, fibroblasts, and smooth muscle cells [ 42 , 48 ]. Contradictory data have been published regarding the toxicity and cytotoxicity of BNNTs, with the potential adverse health effects of this bioceramic restricting their current applications in TE [ 65 ].…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
“…The most dominant cell types used in the included articles were human embryonic kidney cells (HEK293, HEK293T) [24,25,74,81,154], human neuroblastoma cells (SH-SY5Y) [30,64,68,73,76,79,82,155], mouse embryonic fibroblasts (NIH/3T3) [70], human dermal fibroblasts (HDF) [31,36,48,51,55], lung fibroblasts (MRC-5) [65,156], dental pulp fibroblasts [34,41,62], lung epithelium cells (A549) [37,55,74], macrophage cells (RAW 264.7) [49,74], human liver epithelium (HeP G2) [27,28,37], human peripheral blood (NB4) [37], glioblastoma cells (malignant U87 [30,37,156], T98 [80,156]), mammary gland adenocarcinoma cells (MCF-7) [156], N9 murine microglia cells [50], osteoblasts [54,66,75,77], osteoblast precursor cell line derived from mouse musculus calvaria (M3CT3) [47]<...…”
Section: Cell Sourcesmentioning
confidence: 99%
“…The study highlighted the size and aspect ratio and absence of biomolecules that lead to higher toxicity levels in cell cultures [74]. Augustine et al [37] investigated a novel atomic force microscopy (AFM)-based cardiomyocyte assay that reliably assesses the cytotoxicity of BNNTs. High-energy probe sonication was used to modify and control the length of BNNTs [37].…”
Section: In Vitro Studies Stated Bnnts Are Cytotoxicmentioning
confidence: 99%
See 1 more Smart Citation